2016
DOI: 10.1523/jneurosci.4278-15.2016
|View full text |Cite
|
Sign up to set email alerts
|

p75NTR and Its Ligand ProNGF Activate Paracrine Mechanisms Etiological to the Vascular, Inflammatory, and Neurodegenerative Pathologies of Diabetic Retinopathy

Abstract: In many diseases, expression and ligand-dependent activity of the p75NTR receptor can promote pericyte and vascular dysfunction, inflammation, glial activation, and neurodegeneration. Diabetic retinopathy (DR) is characterized by all of these pathological events. However, the mechanisms by which p75 NTR may be implicated at each stage of DR pathology remain poorly understood. Using a streptozotocin mouse model of diabetic retinopathy, we report that p75 NTR is upregulated very early in glia and in pericytes to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
88
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(97 citation statements)
references
References 40 publications
9
88
0
Order By: Relevance
“…Our results are in consistence with previous work that diabetes induced p75 NTR activate NF k B in endothelial cell and activated NF k B act on pericyte through transferring micro particles containing microRNA-503 resulting in decreased VEGF and Ephrin-B2 expression [19]. Our results are also in agreement with a recent report showing that p75 NTR is mediating pericytes loss and diabetes-induced BRB breakdown [16]. …”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…Our results are in consistence with previous work that diabetes induced p75 NTR activate NF k B in endothelial cell and activated NF k B act on pericyte through transferring micro particles containing microRNA-503 resulting in decreased VEGF and Ephrin-B2 expression [19]. Our results are also in agreement with a recent report showing that p75 NTR is mediating pericytes loss and diabetes-induced BRB breakdown [16]. …”
Section: Resultssupporting
confidence: 93%
“…Consistent with our previous report, genetic deletion of p75 NTR suppressed long-term diabetes-induced IL-1β inflammation (Figure 2). We and others have shown that modulating p75 NTR expression or activity significantly reduced TNF-α expression by inhibiting NF k B activation in retina of short term diabetic animals [10,11,16] and in response to stable proNGF over expression [11,30]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The receptor p75 NTR is a novel therapeutic target implicated in many retinal degenerative diseases such as DR, 17 experimental glaucoma, 18 and optic nerve damage. 19 Specifically, studies using a streptozotocin (STZ) mouse model of type I diabetes demonstrated p75 NTR -dependent induction of proinflammatory agents TNFa and a2M, disruption of the neuroglia vascular unit, blood-retina barrier (BRB) breakdown, edema, and ganglion cell neuronal death.…”
mentioning
confidence: 99%